Sexual violence associated with poor mental health in women attending Australian general practices - Laura Tarzia; Sarah Maxwell; Jodie Valpied; Kitty Novy; Rebecca Quake; Kelsey Hegarty (Elsevier, 2017)
Abstract Objective: Sexual violence (SV) against adult women is prevalent and associated with a range of mental health issues. General practitioners could potentially have a role in responding, however, there is little information to help guide them. Data around prevalence of all forms of adult SV (not just rape) is inconsistent, particularly in clinical samples, and the links between other forms of SV and mental health issues are not well supported. This study aimed to address these gaps in the knowledge base. Methods: A descriptive, cross‐sectional study was conducted in Australian general practice clinics. Two hundred and thirty adult women completed an anonymous iPad survey while waiting to see the doctor. Results: More than half the sample had experienced at least one incident of adult SV. Most commonly, women reported public harassment or flashing, unwanted groping and being coerced into sex. Women who had experienced adult SV were more likely to experience anxiety than women who had not, even after controlling for other factors. Women who had experienced adult SV were more likely to feel down, depressed or hopeless than women who had not; however, this association disappeared after controlling for childhood sexual abuse. Conclusions: The findings support the association between SV and poor mental health, even when 'lesser' incidents have occurred. Implications for public health: General practitioners should consider an experience of SV as a possible factor in otherwise unexplained anxiety and depressive symptoms in female patients.